Administrative responsibility and administrative coercion: a synergistic effect of interaction - Vdovichen, Vitalii (Angel Kanchev University of Ruse, 2022)
Taking into account the synergistic effect of the interaction of administrative responsibility and administrative coercion in the system of protection of human rights and freedoms, ensuring public order helps to identify and increase the positive effects of lawmaking, law enforcement and law enforcement. In addition, it should be emphasized that administrative responsibility as one of the priority and leading institutions of administrative law can not be formed in isolation from internal and external factors of legal influence, and at the same time, administrative coercion is one of these areas. Thus, the synergetic effect is also manifested in the interaction of internal and external factors shaping the effectiveness of administrative sanctions for administrative offenses, but the decisive influence in this case can be given to the educational function. However, these functions of administrative responsibility cannot be divided into primary and secondary, their impact is not isolated, but systemic. But the classification of measures of administrative and legal coercion is based on the purpose of applying a particular group of coercive measures. That is, when applying preventive measures, the main goal is to prevent possible offenses and other harmful consequences of catastrophes, accidents, natural disasters, etc., when applying administrative measures - to stop an already started offense and prevent its possible harmful consequences - compensation for property damage and restoration of the state of affairs that existed before the offense, when applying measures to ensure proceedings in cases of administrative offenses - ensuring the appropriate procedural procedure for bringing the perpetrator to administrative responsibility.
Keywords: administrative responsibility; administrative coercion; state conviction; authorized state bodies; state coercion